Comparison of Visual Neuroadaptations After Multifocal and Monofocal Intraocular Lens Implantation - Zhang, Li; Lin, Duoru; Wang, Yong; Chen, Wan; Xiao, Wei; Xiang, Yi; Zhu, Yi; Chen, Chuan; Dong, Xiying; Liu, Yizhi; Chen, Weirong; Lin, Haotian (Frontiers in Neuroscience, 2021)
Visual neuroadaptation is believed to play an important role in determining the final visual outcomes following intraocular lens (IOL) implantation. To investigate visual neuroadaptation in patients with age-related cataracts (ARCs) after phacoemulsification with multifocal and monofocal IOL implantation, we conducted a prospective, controlled clinical trial in Zhongshan Ophthalmology Center. This study included 22 patients with bilateral ARCs: 11 patients underwent phacoemulsification and multifocal IOL (Mu-IOL) implantation, and 11 patients underwent phacoemulsification and monofocal IOL (Mo-IOL) implantation. Visual disturbances (glare and halos), visual function (including visual acuity, retinal straylight, contrast sensitivity, and visual evoked potentials) and visual cortical function (fractional amplitude of low-frequency fluctuations, fALFF) in Bowman’s areas 17-19 as the region of interest were assessed before and after surgeries. The results showed that the fALFF values of the visual cortex in the Mu-IOL group decreased at 1 week postoperatively and recovered to baseline at 3 months and then improved at 6 months, compared with preoperative levels (at a whole-brain threshold of P<0.05, AlphaSim-corrected, voxels >228, repeated measures ANOVA). Significantly increased fALFF values in the visual cortex were detected 1 week after surgery in the Mo-IOL group and decreased to baseline at 3 and 6 months. The fALFF of the lingual gyrus was negatively correlated with visual disturbances (P<0.05). To conclude, early postoperative visual neuroadaptation was detected in the Mu-IOL group by resting-state fMRI analysis. The different changing trends of postoperative fALFF values in the two groups indicated distinct neuroadaptations patterns after Mu-IOL and Mo-IOL implantation.